(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The Civil war in Syria with its different protagonists, scenarios and all elements that make it up can´t be appropriately understood without a retrospective view on recent History. This article deals with a historic perspective about the perceptible confessional matter in Syria which is differentiated in three main periods: the end of the Ottoman Control, the Mandate and the Contemporary State- and has the goal or determining if religion plays an essential role within the conflict or if on the contrary religious beliefs have been used for all different sides as a political or social upheaval instrument. Moreover I will display elements that are considered characteristic in the context of the country´s current situation which have been present in Syria process for more than one and a half century